Uterine receptivity and implantation: The regulation and action of insulin-like growth factor binding protein-1 (IGFBP-1), HOXA10 and forkhead transcription factor-1 (FOXO-1) in the baboon endometrium - Fazleabas Asgerally T; Kim J J (Reproductive Biology and Endocrinology, 2004)
Abstract In primates, the phase of the menstrual cycle when the uterus becomes receptive is initially dependent on estrogen and progesterone. Further morphological and biochemical changes are induced as a result of biochemical signals between the embryo and the maternal endometrium. Blastocyst implantation in the baboon usually occurs between 8 and 10 days post ovulation and is similar to that described for the rhesus macaque. In the baboon, when chorionic gonadotropin is infused in a manner that mimics blastocyst transit, this has physiological effects on the three major cell types in the uterine endometrium. The luminal epithelium undergoes endoreplication and distinct epithelial plaques are evident. The glandular epithelium responds by inducing transcriptional and post-translational modifications in the major secretory product, glycodelin. The stromal fibroblasts initiate their differentiation process into a decidual phenotype and are characterized by the expression of actin filaments. Decidualization, is the major change that occurs in the primate endometrium after conception. During this process the fibroblast-like stromal cells change morphologically into polygonal cells and express specific decidual proteins. Studies in the baboon demonstrated that insulin-like growth factor binding protein-1 (IGFBP-1) gene expression is a conceptus-mediated response. Subsequent studies in vitro established that IGFBP-1 is transcriptionally regulated by FOXO1 and HOXA10 which together upregulate the IGFBP-1 promoter activity. A baboon endometriosis model was utilized to determine if the changes observed during uterine receptivity in normally cycling animals were compromised. The data suggests that in animals with disease, markers of uterine receptivity are not appropriately expressed in the eutopic endometrium. It is possible that these differences influence the fertility of the animals with disease and the baboon could be used as a primate model to study the causes of infertility as a result of endometriosis.